Optimization of traction energy consumption using intelligent rail traffic management systems - Janusz Szkopiński (Przegląd Komunikacyjny)
Abstract: The subject of this work is the analysis of the benefits of implementing intelligent railway traffic management systems with regard to achieving smooth train operation and, consequently, reducing the train’s traction energy consumption. The analysis refers to technical solutions used on European railways that enable the optimization of train traffic. One of the factors allowing such optimization is the shaping of the train’s speed profile so that the travel time to a signal showing “Stop” is not shorter than the expected time until the signal changes to allow further travel. As part of this analysis, traffic simulations were carried out based on the ETR610 ED250-type train model, for different variants of train speed control and two variants of the preliminary distance to the signal. The result of the work includes observations on the possibility of implementing intelligent railway traffic management systems, including a comparison of possible savings in traction energy consumption.